P483 Golimumab response in Ulcerative Colitis as early as week 2: What can we take from this?. (30th January 2023) - Kumar, L; O'Morain, N; Sheridan, J; Coe, C; Egan, C; Jones, F; Cullen, G; Doran, P; Leyden, J; Galligan, M; McCarthy, J; O'Toole, A; et al.
Abstract: Background: Golimumab is a monoclonal anti-TNF drug used in the treatment of Ulcerative Colitis (UC). GOAL-ARC is a multi-centered investigator initiated randomized control trial seeking to evaluate the utility of personalized Golimumab dose adjustment in UC versus standard dosing as per summary of product characteristics (SMPC) post-induction. From early analysis data, we aimed to ascertain if Golimumab induces response at 2 weeks and if this early response impacts disease activity at 6 weeks and the need for dose escalation at this interval. Methods: Patients recruited to the trial were randomized to an intervention or a standard dosing arm. Golimumab was administered at 200mg at week 0 and 100mg at week 2 with assessments at weeks 0, 2, and 6. Baseline data was obtained including patient demographics and burden of disease. Outcomes measured were clinical response (defined by a decrease in partial mayo score of 2 points or a decrease of ≥30% from baseline), change in Faecal Calprotectin (FCP) as well as improvement in Short Health Scale (SHS) score and serum golimumab levels at 6 weeks. We also looked at FCP≤250μg/g (STRIDE II – intermediate treatment target) as an outcome. Results: A total of 94 patients were recruited with 90 (95.7%) patients completing 2-week follow up and 79 (84%) patients completing 6-week follow-up. The median age was 37 years (IQR 28-46), 58.5% were male, and 76.6% (n=72) had a Mayo endoscopic subscore of 2 and the median DUBLIN Score was 4 (IQR 4-6). At 2 weeks, a clinical response was observed in 68.9% of patients (n=62). There was a significantly lower median modified partial mayo score (2 vs 4, p<0.001), rectal bleeding score (0 vs 2, p<0.001), stool frequency score (1 vs 2, p<0.001) and total SHS score (21.0 vs 25.8, p<0.001) after 2 weeks of treatment. The median FCP was numerically lower (354.7μg/g vs 1111.5μ/g, p=0.207) with an overall reduction by 32.5%. Patients who achieved a clinical response at 2 weeks were noted to have a lower baseline total SHS score (23.9 vs 29.0, p=0.017). 2-week response did not correlate with 6-week outcomes. Median FCP was significantly lower at 6 weeks (254.2μg/g vs 1111.5μ/g, p=0.008) with an overall reduction by 74.0%. There was a significantly higher median Golimumab level in patients with FCP≤250μg/g at 6 weeks (5.59μg/ml vs 2.41μg/ml, p<0.001). Conclusion: Golimumab shows efficacy in Ulcerative Colitis as early as 2 weeks with significant clinical response and a biochemical response. Early data suggests that response at 2 weeks, however, is not a reliable indicator of a sustained clinical response.